2019
DOI: 10.1002/jcp.29204
|View full text |Cite
|
Sign up to set email alerts
|

Role of liraglutide in brain repair promotion through Sirt1‐mediated mitochondrial improvement in stroke

Abstract: Brain repair, especially axonal sprouting, is critical to restore motor function in disabled stroke patients. Liraglutide (LG) is a new kind of long-acting analogue of glucagon-like peptide-1 (GLP-1) and has potential protective effects in stroke. The mitochondria participate in brain repair after cerebral injury. However, the mechanism of the effect of LG on brain repair and its potential influence on mitochondria in stroke remains obscure. Here, in focal cerebral cortical ischemic mice model, LG improved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 47 publications
1
28
1
Order By: Relevance
“…A similar profile was observed in the hippocampus, and microglia burden was reduced after EMP treatment in SP-free areas (close to plaques ([F (3,39) =2.21, p = 0.91]); far from plaques [F (7, 768) = 23.79, ╫╫ p < 0.01 vs. control, control-EMP, APP/ PS1, APP/PS1-EMP, and APP/PS1xdb/db-EMP, † † p < 0.01 vs. control, control-EMP, APP/PS1-EMP, and APP/PS1xdb/db-EMP, ♯♯ p < 0.01 vs. control and control-EMP]) (control n = 5, control-EMP n = 5, APP/PS1 n = 5, APP/PS1-EMP n = 4, db/db n = 6, db/db-EMP n = 4, APP/PS1xdb/db n = 4, APP/ PS1xdb/db-EMP n = 5). density after long-term administration, as previously described with other antidiabetic treatments [12,35,36]. Vascular disease has been closely associated to AD and T2D, and a synergistic effect has been reported when both pathologies coexist.…”
Section: Discussionsupporting
confidence: 55%
“…A similar profile was observed in the hippocampus, and microglia burden was reduced after EMP treatment in SP-free areas (close to plaques ([F (3,39) =2.21, p = 0.91]); far from plaques [F (7, 768) = 23.79, ╫╫ p < 0.01 vs. control, control-EMP, APP/ PS1, APP/PS1-EMP, and APP/PS1xdb/db-EMP, † † p < 0.01 vs. control, control-EMP, APP/PS1-EMP, and APP/PS1xdb/db-EMP, ♯♯ p < 0.01 vs. control and control-EMP]) (control n = 5, control-EMP n = 5, APP/PS1 n = 5, APP/PS1-EMP n = 4, db/db n = 6, db/db-EMP n = 4, APP/PS1xdb/db n = 4, APP/ PS1xdb/db-EMP n = 5). density after long-term administration, as previously described with other antidiabetic treatments [12,35,36]. Vascular disease has been closely associated to AD and T2D, and a synergistic effect has been reported when both pathologies coexist.…”
Section: Discussionsupporting
confidence: 55%
“…There have been many reports that SIRT1 can be a target of herbal medicines [30]. However, in this study neither tMCAO or the pre-administration of AGmex had any effect on SIRT1 expression ( Fig.…”
Section: Discussioncontrasting
confidence: 49%
“…43 Nine studies reported a reduction in neurological deficit when GLP-1RAs were administered to normoglycemic models at least 1 hour after induction of AIS. [32][33][34][35][36]41,43,47,49 Notably, Filchenko et al reported that whilst reduction in neurological deficit was observed in the non-diabetic rat model treated with liraglutide, this trend was not observed in the diabetic groups. 31 Potential mechanisms:…”
Section: Neurological Outcomesmentioning
confidence: 99%
“…However, whilst there are some reports of Ex-3-9 administration blocking neuroprotection, 21 suggestive of GLP-1R dependence, other studies did not demonstrated this trendhighlighting the possibility of a GLP-1R independent mechanism 41,46. For example, GLP-1[28][29][30][31][32][33][34][35][36] is cleaved from endogenous GLP-1; research has shown this cell-permeable nonapeptide to have antioxidant, anti-apoptotic and mitochondrial regulatory properties in pancreatic cellsfurther research is required to establish its role in neural tissue59 .…”
mentioning
confidence: 99%